Composition law of oblique anhysteretic remanent magnetization and its relation to the magnetostatic interaction. (21st March 2017) - Sato, Masahiko; Mochizuki, Nobutatsu; Watanabe, Minako; Tsunakawa, Hideo
Abstract: The basic properties of oblique anhysteretic remanent magnetization (OARM) acquired in a weak and steady magnetic field with an arbitrary angle to the alternating field direction were studied. OARM and rock‐magnetic experiments were conducted on samples of basalt, granite, and sediment containing noninteracting single domain (SD), interacting SD, pseudo‐single‐domain, and multidomain low‐Ti titanomagnetites. The intensity of OARM ( M OARM ) systematically increased or decreased with increasing angle between alternating and steady field directions ( θ SF ), while the angle between alternating field and OARM directions ( θ OARM ) increased with increasing θ SF for all samples. During stepwise alternating field demagnetization, the OARM vector shows a single component parallel to the steady field direction for θ SF = 0° (ARMǁ ) and 90° (ARM⊥ ). The median destructive field of ARM⊥ is larger than that of ARMǁ . For intermediate angles ( θ SF = 30°, 45°, and 60°), the OARM vector did not parallel the applied steady field but gradually increased θOARM with higher coercivity. These experiments indicate that the OARM vector is approximately given by the sum of two orthogonal magnetizations coinciding with ARMǁ and ARM⊥, respectively. Thus, the OARM vector can be determined by acquisition efficiencies of ARMǁ and ARM⊥ in an individual sample. Based on these experiments and associated rock‐magnetic measurements, noninteracting SD samples show lower ARM⊥ /ARMǁ ratios, compared to other samples. This result suggests that OARM can be used as a useful tool to detect noninteracting SD particles in the paleomagnetic samples. Key Points: Intensity and direction of OARM systematically change with angle between alternating and steady magnetic field directions OARM vector is approximated to the composition of parallel‐ARM and perpendicular‐ARM vectors OARM can be used as a useful tool to detect noninteracting SD particles in paleomagnetic sample